Tatalaksana sindroma Wolf-Parkinson-White terselubung pada pasien dengan Alat Pacu Jantung - Daf Juzar; Yoga Yuniadi; Muhammad Munawar (Jurnal Kardiologi Indonesia, 2007)
Wolf-Parkinson-White syndrome is part of the supraventricular tachycardias, which are relatively common, often repetitive, occasionally persistent and rarely life threat-ening. Management of atrioventricular reciprocating tachycardia (AVRT) in patients with permanent pacemaker (PPM) is rarely being discussed. We would like to report our experience in the management of two cases with AVRT, one on VVIR and another one on AAI. In the first case catheter ablation of the atrioven-tricular juction was performed, while in the second case arrhythmia was termi-nated using burst pacing.